2015
DOI: 10.1103/physrevd.92.094503
|View full text |Cite
|
Sign up to set email alerts
|

Potential description of charmonium and charmed-strange mesons from lattice QCD

Abstract: We present spin-independent and spin-spin interquark potentials for the charmonium and charmed-strange mesons, which are calculated in 2+1 flavor lattice QCD simulations using the PACS-CS gauge configurations generated at the lightest pion mass (Mπ ≈ 156(7) MeV) with a lattice cutoff of a −1 ≈ 2.2 GeV and a spatial volume of (3 fm) 3 . For the charm quark, we use a relativistic heavy quark (RHQ) action with fine tuned RHQ parameters, which closely reproduce both the experimental spin-averaged mass and hyper-fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 95 publications
11
38
0
Order By: Relevance
“…The spin triplet states χ cJ are in good agreement with both experiment and other phenomenological models. The lattice QCD obtains the masses 20 − 25 MeV smaller than the experimental val-ues for these states [61]. We have also predicted masses of low lying D wave states which is reasonably in good agreement with available experimental data [56]and with other theoretical models [58], [59], [60] The spin-orbit and tensor potentials in eqn(6) are responsible for the splitting of the charmonium levels.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The spin triplet states χ cJ are in good agreement with both experiment and other phenomenological models. The lattice QCD obtains the masses 20 − 25 MeV smaller than the experimental val-ues for these states [61]. We have also predicted masses of low lying D wave states which is reasonably in good agreement with available experimental data [56]and with other theoretical models [58], [59], [60] The spin-orbit and tensor potentials in eqn(6) are responsible for the splitting of the charmonium levels.…”
Section: Resultssupporting
confidence: 85%
“…The mass of spin-singlet P-wave charmonium h c (1P ) is in good agreement with experiment and other theoretical models. However the lattice QCD predicts a mass of 3506 ± 6 MeV for h c (1P ) state which is slightly below the experimental value [61]. The spin triplet states χ cJ are in good agreement with both experiment and other phenomenological models.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Although we only focused on the BS wave function of the ground state in the previous works [13][14][15][16], we here intend to obtain the BS wave function of the radially excited states. For this purpose, we adopt the variational method [17,18] to find an optimal meson operator O opt n , which solely couples to a specific (nth) state in Eq.…”
Section: A Bs Wave Functions Determined Through the Variational Methodsmentioning
confidence: 99%
“…In the past several years, we have demonstrated that the interquark potential and the quark kinetic mass, both of which are key ingredients within the potential description of heavy-heavy and heavy-light mesons, are successfully determined from the BS wave functions of the ground state of S-wave charmonium and charm-strange mesons [14][15][16]. A natural question arises: if we simply apply our proposed method on not only the ground state, but also its excited states, what result comes out, especially from the BS wave function of radially excited states?…”
Section: B Quark Kinetic Mass and Interquark Potential From Bs Amplimentioning
confidence: 99%